Final Report to the National Endowment for the Humanities for Hiram College. The Hiram College Freshman Year Program - Morgan, George A.; Hiram Coll., OH. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This report presents a summary and evaluation of the new freshman curriculum at Hiram College. The curriculum, established in the fall of 1969, is based upon the premise that by giving freshmen more freedom and responsibility, along with the opportunity for more individual faculty guidance, a college can create an atmosphere in which both academic inquiry and personal growth will flourish. The curriculum consists of 3 components: the Freshman Institute, the Freshman Colloquia, and the Twentieth Century and Its Roots Course. The content of the focus of the 2-week Freshman Institute was on language and effective communication. It is felt that the Institute was successful in increasing student emphasis on responsible and articulate expression. The freshman Colloquia, also judged quite valuable, consisted of small groups of 10-12 students with a faculty advisor. This component continued the emphasis on the personal dimension of education by improving communication skills, dealing seriously with academic topics, and by exposing the students to humane, moral, and aesthetic concerns. The final component of the freshman program, the "Twentieth Century and Its Roots Course," was only moderately well received-in it students examined the major issues of modern society from many perspectives. Although this course was not as well attended as expected, it is hoped that it will gain greater student interest in subsequent semesters. (HS)
Sponsoring Agency: National Endowment for the Humanities (NFAH), Washington, DC.
Contract Number: H69-0-121.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; College Students; Curriculum; Educational Innovation; Experimental Programs; Higher Education; Program Evaluation